A conceptual analysis of maltreatment in sports: A sport social work perspective - Gattis, Courtney; Moore, Matt (Frontiers in Sports and Active Living, 2022)
Maltreatment in sports is an epidemic and occurs in many relational forms such as physical, sexual, and emotional abuse or neglect. Maltreatment in sports also exists in forms of non-relational abuse and focuses on mezzo and macro forms of maltreatment such as systematic abuse, organizational abuse, and physiological abuse or neglect (e.g., exploitation and athlete trafficking). It is imperative to study the effects of maltreatment in sports as athletes can be the victims (survivors) as well as perpetrators of abuse. Recent research in the field of social work points to the benefits of Trauma-Informed Sports and Short Focused Brief Therapy (SFBT) as possible interventions. It is imperative for transferability in the field of maltreatment in sports, that practitioners define each form of abuse in the context of maltreatment and trauma. This commentary aims to discuss the different forms of maltreatment in sports that could affect athletes and provide discussion and insights into the void of research surrounding certain forms of non-relational abuse and the role trauma-informed therapies serve in promoting athlete wellbeing from a social work lens.